Effectiveness and safety of an emergency department-based rapid response system - Fanny Delfanti; Guido Bertolini; Giovanni Nattino; Giulia Acquistapace; Daniela De Palma; Piergiuseppe Ferrari; Sara Martinenghi; Stefano Maiandi; Marco Rossi; Anna Lilia Ruocco; Maria Teresa Spina; Benedetta Chiodi; et al. (Emergency Care Journal)
Rapid Response Systems (RRSs) are designed to assist hospitalized patients who become unstable, aiming to address “failure to rescue” and prevent cardiac arrests. Despite global implementation, evidence of RRS effectiveness is controversial. This study evaluates the effectiveness and safety of an RRS at Maggiore Hospital in Lodi, Italy, focusing on the Medical Emergency Team (MET) organization. The RRS at Maggiore Hospital was established in 2017 using the National Early Warning Score (NEWS) for monitoring. The MET, consisting of an emergency physician and one nurse, operates from 8:00 PM to 8:00 AM. Data from 2014-2019, divided into PRE (2014-2016) and POST (2017-2019) periods, were analyzed. The primary outcomes were unplanned ICU transfers and in-hospital mortality. A difference-in-differences (DiD) design compared outcomes in MET and non-MET wards before and after RRS implementation. Hospitalizations were similar in the PRE and POST periods. A significant reduction in Intensive Care Unit (ICU) transfers was observed overall (0.26%, p=0.005), but not in mortality (0.10%, p=0.47). Both MET and non-MET wards showed reduced ICU transfers, but the decrease was statistically significant only in MET wards. DiD analysis showed no significant reductions in either ICU transfer (p=0.77) or mortality rates (p=0.15) between MET and non-MET wards. The RRS at Maggiore Hospital effectively reduced ICU transfers without increasing mortality, demonstrating its safety. The MET organization did not significantly impact ICU transfers compared to non-MET wards. Further studies should explore additional measures of clinical deterioration to fully assess the impact of RRS.